AN ANALYSIS OF SYNTACTICAL ERRORS IN STUDENTS’ WRITING AT 11TH GRADE MA MUALIMIN MUHAMMADIYAH BOARDING SCHOOL SAWAH DANGKA - Suci Febri Yanni; Eliza; Loli Safitri (Fakultas Keguruan dan Ilmu Pendidikan, 2021)
The research was caused by several problems that were discovered in students' writing recount text. First, students make errors in their sentences. One error that occurs in their sentences is the omission of verbs. Students make sentences without verbs in writing recount text. Secondly, students only arrange sentences based on the words in the dictionary so that it causes mother tongue interference. This research aimed to investigate the errors in students' writing at syntactical error and causes of error in students' writing. The research used descriptive qualitative research. The data was collected from the students' writing recount in class 11 A of MA Mualimin Muhammadiyah Boarding School Sawah Dangka. The technique of data analysis in this research was identification, classification, explanation, and evaluation. The finding of the research shows, Firstly. Syntactical errors occurred in the omission, addition, misformation, and misordering, which included noun phrases, verb phrases, and verb and verb construction. Noun phrases included determiner, pronoun, and preposition. Verb phrase included the omission of verb and subject and verb agreement. Then, verb and verb construction. Secondly, the two major causes of errors were interlingual transfer and intralingual transfer.